Hospital Waste Management in Kidney Transplantation Procedure: Implications and Solutions - Eriawan Agung Nugroho; Leonardo Cahyo Nugroho (Waste Technology, 2019)
The number of patients diagnosed with end-stage renal disease (ESRD) in Indonesia is increasing annualy, showing a similar trend with the global prevalence. Withits superior outcome, kidney transplantation remains to be the traetment of choice for ESRD. The treatment with transplant kidney procedure makes extensive use of presterilized disposable items which, after use, are contaminated by blood. The preferred route of disposal of such items is by incineration. Disposal costs have risen and this increase in costs has not been matched by waste management programs in kidney transplantation procedure. Many of the waste items like container for blood products and intravenous infusion fluid contain erwhichiswidely used in kidney transplantation procedure generated alsoconta in polyvinylchloride (PVC) whose incineration is environmentally sensitive. Furthermore blood tubing sets contain plasticizers such as di(2-ethylhexyl) phthalate (DEHP), which is known to pose health risks to specific groups of patients. The generation of hospital waste in a kidney transplantation procedure is analyzed, issues associated with disposal are discussed, and approaches toward a cost effective environmentally sustainable hospital waste management program are reviewed.